Assessing the Assurance of Legal Certainty and Equity of the Indonesian Law of Money Laundering - Seno Wibowo Gumbira; Umi Khaerah Pati; Kukuh Tejomurti; Ratna Nurhayati (Faculty of Law, Universitas Padjadjaran, 2022)
Law of Money Laundering has a fundamental point to eradicate transnational predicate and serious crimes. Each state has different arrangements to address predicate crime. Indonesia considers predicate crime in the category of ordinary crime consisting of fraud and embezzlement. However, ordinary or conventional crimes may only be subject to the Law under limited circumstances. Article 69 of the Law of Money Laundering remains debatable among criminal law experts due to the relation with Articles 77 and 78 of the Law. The last two articles prescribe that burden of proof on the case of predicate crimes is on defendant, not public prosecutor. Defendant must prove assets that are suspected as result of crime, not acquired from the crime, or related to crime. Currently, there is no elucidation to the articles. This study analyzed two legal issues. Firstly, does the formulation of Article 2, paragraph 1, and Article 69 of the Law of Anti-Money Laundering guarantee legal certainty and fulfil a sense of justice? Secondly, does the Article 2 paragraph 1 letter z of the Law cause ordinary criminal acts to be entangled with the Law on Money Laundering?DOI: https://doi.org/10.22304/pjih.v9n1.a1